Corporate social responsibility and financial performance during the COVID-19 pandemic : Evidence from Nordic firms - Tenhovuori, Laura (My University, 2022)
The relationship between corporate social responsibility and financial performance has been an ongoing subject relating to whether firms should invest in CSR activities or not. The question is do the benefits outweigh the costs, but unfortunately, research in the field has found inconclusive results. The COVID-19 pandemic presents an unexpected external shock to the stock market, which allows for a setting to examine whether firms engaging in CSR activities outperform companies with lower amounts of CSR engagement. This thesis examines the relationship between corporate social responsibility and corporate financial performance during the COVID-19 pandemic. The main questions under investigation are whether companies with higher CSR ratings outperform companies with lower CSR ratings. Also, the study aims to answer whether there is a relationship between CSR scores and volatility during times of pandemics. The study is conducted using a Nordic sample of firms listed on the stock exchanges and that have received CSR-related ratings. In this thesis, the Nordic countries consist of Denmark, Finland, Norway, and Sweden. The sample also allows for examining how different lockdown procedures affected corporate financial performance. Although the Nordic countries have similar characteristics, governmental structures, and demographics, Sweden decided on different social distancing measures compared to the other Nordics in the sample. The study uses both market-based and accounting-based measures to evaluate corporate financial performance during the pandemic. Dependent variables that are implemented include stock returns, volatility, and operating performance measures. The results are obtained using cross-sectional regressions and difference-in-differences regressions. Using two types of regressions allows for a broader analysis of the effects of the pandemic. In addition, the thesis incorporates robustness tests to evaluate the results further. The results of the study suggest that companies with high CSR ratings are not superior to those with lower CSR scores. Regressions with quarterly abnormal returns as dependent variables suggest the opposite. When studying yearly abnormal returns, the results are not statistically significant. In countries that implemented social distancing measures, the quarterly abnormal returns are negatively correlated with ES scores. The study finds a negative relationship between CSR and operational performance, but this is based on one model of six. The results for a negative relationship are also found in the Swedish sample, but not in a sample consisting of the countries that implemented stricter social distancing measures. Furthermore, the results suggest a significant and negative correlation between CSR and volatility. The results are the same in all Nordic countries.

Vastuullisuuden ja yrityksen taloudellisen suorituskyvyn välinen suhde on ollut jatkuva puheenaihe liittyen siihen pitäisikö yrityksen investoida vastuullisiin toimintatapoihin vai ei. Kysymyksenä on, ovatko vastuullisuuden tuomat hyödyt kustannuksia suuremmat, mutta aiempi tieteellinen tutkimus ei ole löytänyt tähän yhtä oikeaa vastausta. COVID-19 pandemia on eräänlainen ulkopuolinen odottamaton shokki osakemarkkinoille. Tämä mahdollistaa sen tutkimisen, suoriutuvatko yritykset, jotka ovat investoineet enemmän vastuullisuuteen paremmin kuin yritykset, joilla on vähemmän vastuullisuuteen tähtääviä investointeja. Tämä tutkielma tarkastelee vastuullisuuden ja yrityksen taloudellisen suorituskyvyn suhdetta COVID-19 pandemian aikana. Tutkimuksen pääkysymyksenä on, suoriutuvatko korkeammalle luokitellut yritykset paremmin kuin yritykset, joilla on matalammat vastuullisuusluokitukset. Tutkielma pyrkii myös löytämään vastauksen siihen, onko vastuullisuusluokitusten ja volatiliteetin välillä suhde pandemiatilanteessa. Tutkimuksessa on käytetty pohjoismaista kohdejoukkoapörssilistatuista yrityksistä, joilla on vastuullisuusluokitukset. Tässä tutkimuksessa pohjoismaat koostuvat Tanskasta, Suomesta, Norjasta ja Ruotsista. Kohdejoukko mahdollistaa myös erilaisten rajoituskäytäntöjen vaikutuksen tutkimisen. Vaikka pohjoismaita kuvataan samankaltaisiksi piirteiltään, valtion rakenteiltaan sekä väestörakenteeltaan, Ruotsin rajoitustoimenpiteet COVID-19 aikana olivat erilaiset kuin muissa kohdejoukon maissa. Tutkielmassa käytetään sekä markkinaehtoisia että kirjanpitoon perustuvia muuttujia mittaamaan yrityksen taloudellista suoriutumista pandemian aikana. Riippuvaisia muuttujia ovat osaketuotot, volatiliteetti sekä taloudellista suoriutumiskykyä mittaavat tunnusluvut. Empiirisessä osiossa käytetään kahdenlaisia regressiomalleja, mikä mahdollistaa laajemman näkökulman kysymyksien vastaamiseen. Tutkielman tulokset osoittavat että yritykset, joilla on korkeat vastuullisuusluokitukset eivät suoriudu paremmin kuin yritykset, joilla on matalammat vastuullisuusluokitukset. Kvartaalikohtaiset ylituotot näyttävät osoittavan päinvastaista. Kun tarkastelussa on vuoden ylituotto, tulokset eivät ole tilastollisesti merkitseviä. Maissa, joissa tiukemmat rajoitustoimenpiteet otettiin käyttöön, kvartaalikohtaiset ylituotot ovat negatiivisesti korreloituneita vastuullisuusluokitusten kanssa. Tutkielman tulokset osoittavat myös negatiivisen suhteen vastuullisuuden ja taloudellisen suoriutumiskyvyn välille. Tämä tulos on nähtävissä ruotsalaisten yhtiöiden keskuudessa, mutta ei muissa pohjoismaissa. Lisäksi tulokset osoittavat tilastollisesti merkitsevän negatiivisen korrelaation vastuullisuuden ja volatiliteetin välille.
Keywords: COVID-19; Nordic countries; corporate responsibility; social responsibility; Sweden; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance